Validation practices for satellite‐based Earth observation data across communities. (21st September 2017) - Loew, Alexander; Bell, William; Brocca, Luca; Bulgin, Claire E.; Burdanowitz, Jörg; Calbet, Xavier; Donner, Reik V.; Ghent, Darren; Gruber, Alexander; Kaminski, Thomas; Kinzel, Julian; Klepp, Christian; et al.
Abstract: Assessing the inherent uncertainties in satellite data products is a challenging task. Different technical approaches have been developed in the Earth Observation (EO) communities to address the validation problem which results in a large variety of methods as well as terminology. This paper reviews state‐of‐the‐art methods of satellite validation and documents their similarities and differences. First, the overall validation objectives and terminologies are specified, followed by a generic mathematical formulation of the validation problem. Metrics currently used as well as more advanced EO validation approaches are introduced thereafter. An outlook on the applicability and requirements of current EO validation approaches and targets is given. Key Points: First review of EO validation approaches across different Geoscience communities Validation approaches depend on the intermittency and inhomogeneity of the geophysical variables Enhanced traceability in EO validation approaches required